2020
DOI: 10.48550/arxiv.2012.00036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancient Very Metal-Poor Stars Associated With the Galactic Disk in the H3 Survey

Courtney Carter,
Charlie Conroy,
Dennis Zaritsky
et al.

Abstract: Ancient, very metal-poor stars offer a window into the earliest epochs of galaxy formation and assembly. We combine data from the H3 Spectroscopic Survey and Gaia to measure metallicities, abundances of α elements, stellar ages, and orbital properties of a sample of 482 very metal-poor (VMP; [Fe/H]< −2) stars in order to constrain their origins. This sample is confined to 1 |Z| 3 kpc from the Galactic plane. We find that > 70% of VMP stars near the disk are on prograde orbits and this fraction increases toward… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
(48 reference statements)
1
5
1
Order By: Relevance
“…By selecting stars at higher vertical distance from the disk and without imposing a selection on 𝐽 𝑧 , we now select stars with orbits farther from the disk, which leads to a somewhat smaller prograde bias. Again, our simulation suite broadly agrees with MW observations from Carter et al (2020), although less well than with the results of Sestito et al (2020). At −2.5 < [Fe/H] < −1, the observations are consistent with being constant, but they show an upward trend at lower [Fe/H].…”
Section: Comparison With the H3 Surveycontrasting
confidence: 41%
See 4 more Smart Citations
“…By selecting stars at higher vertical distance from the disk and without imposing a selection on 𝐽 𝑧 , we now select stars with orbits farther from the disk, which leads to a somewhat smaller prograde bias. Again, our simulation suite broadly agrees with MW observations from Carter et al (2020), although less well than with the results of Sestito et al (2020). At −2.5 < [Fe/H] < −1, the observations are consistent with being constant, but they show an upward trend at lower [Fe/H].…”
Section: Comparison With the H3 Surveycontrasting
confidence: 41%
“…Recently, the H3 Spectroscopic Survey (Conroy et al 2019) also examined the orbits of metal-poor ([Fe/H] < −2) stars in the MW's halo (out of the disk; Carter et al 2020). They also found a strong prograde bias, with nearly 70 per cent of their stars on prograde orbits (defined as 𝐽 𝜙 > 0), in general agreement with (Sestito et al 2020), though Carter et al (2020) found some evidence that the prograde bias increases at lower [Fe/H] as well. Figure 3 (crosses with uncertainties) shows their results.…”
Section: Comparison With the H3 Surveymentioning
confidence: 99%
See 3 more Smart Citations